2022
DOI: 10.2147/ijn.s338334
|View full text |Cite
|
Sign up to set email alerts
|

The Immune-Enhancing Properties of Hwanglyeonhaedok-Tang-Mediated Biosynthesized Gold Nanoparticles in Macrophages and Splenocytes

Abstract: Background: Despite great advances in the field of immunotherapy, there is still a need for novel and effective immunostimulants to overcome challenges, such as instability and autoinflammatory toxicity, associated with conventional immunostimulants. Nanotechnology provides the possibility to overcome these challenges. The well-known classical Chinese formula, Hwanglyeonhaedok-tang (HHT) has been widely used to treat immune-related diseases in clinical practice. Methods: We developed novel gold nanoparticles (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Immune cells are the first barrier for nanoparticles to penetrate into cells ( 50 ). It is necessary to study the uptake of nanoparticles by macrophages, which is essential for nanoparticles to exert their effects and potentially induce a toxic response.…”
Section: Resultsmentioning
confidence: 99%
“…Immune cells are the first barrier for nanoparticles to penetrate into cells ( 50 ). It is necessary to study the uptake of nanoparticles by macrophages, which is essential for nanoparticles to exert their effects and potentially induce a toxic response.…”
Section: Resultsmentioning
confidence: 99%
“…So-yeom pharmacopuncture contains the same active constituent as HHT, and was expected to exert a similar effect to HHT tablets [19]. The HHT tablets were expected to reduce the heat sensation and pain of unknown origin by increasing nitric oxide and immune-related cytokines to increase immunity [20]. However, because HHT tablets were started on Day 8, it is recognized that the treatment tools should have been implemented uniformly for similar cases in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Splenocytes are composed of various types of immune cells. Activated splenocytes elicit subsequent immune system activation by releasing various cytokines [ 24 , 25 ]. IFN-γ is a major immunostimulatory cytokine involved in cellular immunity, including both innate and adaptive immune cells [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is a pleiotropic cytokine that plays multiple roles in the regulation of hematopoiesis, immune responses, and acute phase reactions, and is broadly secreted not only by activated lymphocytes but also by various types of non-lymphoid cells [ 28 ]. Many studies have established these cytokines as biomarkers that support immunostimulation through splenocyte activation [ 25 , 29 ]. We confirmed that the production of IFN-γ, TNF-α, and IL-6 was significantly increased in splenocytes by oral administration of PLME ( Figure 3 b–d), suggesting activation of the spleen-mediated immune system following PLME consumption.…”
Section: Discussionmentioning
confidence: 99%